1984
DOI: 10.1037/0033-295x.91.2.235
|View full text |Cite
|
Sign up to set email alerts
|

Stress and affiliation: A utility theory.

Abstract: Available affiliation theories are unable to explain apparent inconsistencies among studies of affiliation tendencies during stressful situations. A new theory, the utility affiliation theory, was suggested to integrate these data into one theoretical framework. The basic assumption of the theory is that the strength of the affiliation tendency is a function of the extent of perceived benefit and damage that may be caused by being with others. The benefit/damage perception may be affected by three basic variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 58 publications
10
59
0
Order By: Relevance
“…The stress-attachment link in adulthood also received some support in studies testing Schachter's (1959) fear-affiliation hypothesis. In these studies, fearful persons are more likely than nonfearful persons to affiliate with an available other while awaiting some noxious event (see Rofe, 1984, andKlinnert, 1982, for reviews). Although this finding has been initially interpreted in terms of social comparison, more recent findings (Kirkpatrick & Shaver, 1988) suggest that stress increases proximity seeking as a means of alleviating distress.…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The stress-attachment link in adulthood also received some support in studies testing Schachter's (1959) fear-affiliation hypothesis. In these studies, fearful persons are more likely than nonfearful persons to affiliate with an available other while awaiting some noxious event (see Rofe, 1984, andKlinnert, 1982, for reviews). Although this finding has been initially interpreted in terms of social comparison, more recent findings (Kirkpatrick & Shaver, 1988) suggest that stress increases proximity seeking as a means of alleviating distress.…”
Section: The Current Studymentioning
confidence: 99%
“…One possibility is to ob-serve a person's behavior and to rate the extent he or she seeks for proximity or support. This methodological strategy has been used in studies with infants (e.g., Ainsworth, 1973;Lamb, 1976), in experiments testing Schachter's (1959) fear-affiliation hypothesis (see Rofe, 1984, for a review), and in recent adult attachment studies (e.g., Rholes, Simpson, & GrichStevens, 1998;Simpson, Rholes, & Nelligan, 1992). The problem with this strategy is that proximity-seeking behaviors may depend on a conscious deliberation about the expected utility and personal-cultural adequacy of these behaviors.…”
Section: The Current Studymentioning
confidence: 99%
“…Previous research showed that the need to belong is especially prevalent under social threat (Elder & Clipp, 1988;Hogg, 2000;Hogg, Sherman, Dieselhuis, Maiter, & Moffitt, 2007;Rofe, 1984). Therefore, to experimentally increase the need to belong to one's group, we threatened participants' perceived ability to recognize faces of in-group members.…”
Section: Studymentioning
confidence: 98%
“…One of the things that happens when people are threatened, or placed in a situation of fear, is that their groups become more important to them (Elder and Clipp 1988;Rofe 1984). One of the things that happens when people are threatened, or placed in a situation of fear, is that their groups become more important to them (Elder and Clipp 1988;Rofe 1984).…”
Section: Groups Fear and Threatmentioning
confidence: 99%